Frequent occurrence of RASSF1A promoter hypermethylation and merkel cell polyomavirus in merkel cell carcinoma - Helmbold, Peter; Lahtz, Christoph; Enk, Alexander; Herrmann-Trost, Peter; Marsch, Wolfgang Christian; Kutzner, Heinz; Dammann, Reinhard (Molecular carcinogenesis, 2009)
skin cancer tumor suppressor gene virus infection DNA methylation epigenetics